Cardiac Resynchronisation Therapy and Cellular Bioenergetics: Effects Beyond Chamber Mechanics - Christos-Konstantinos Antoniou (Radcliffe Medical Media, 2019)
Cardiac resynchronisation therapy is a cornerstone in the treatment of advanced dyssynchronous heart failure. However, despite its widespread clinical application, precise mechanisms through which it exerts its beneficial effects remain elusive. Several studies have pointed to a metabolic component suggesting that, both in concert with alterations in chamber mechanics and independently of them, resynchronisation reverses detrimental changes to cellular metabolism, increasing energy efficiency and metabolic reserve. These actions could partially account for the existence of responders that improve functionally but not echocardiographically. This article will attempt to summarise key components of cardiomyocyte metabolism in health and heart failure, with a focus on the dyssynchronous variant. Both chamber mechanics-related and -unrelated pathways of resynchronisation effects on bioenergetics – stemming from the ultramicroscopic level – and a possible common underlying mechanism relating mechanosensing to metabolism through the cytoskeleton will be presented. Improved insights regarding the cellular and molecular effects of resynchronisation on bioenergetics will promote our understanding of non-response, optimal device programming and lead to better patient care.